Effect of Bio-phosphate on Increasing the Phosphorus Availability, the Growth and the Yield of Lowland Rice in Ultisol - Yafizham Yafizham; Muslim Abubakar (JOURNAL OF TROPICAL SOILS, 2010)
Effects of Bio-phosphate on Increasing the Phosphorus Availability, the Growth and the Yield of Lowland Rice in Ultisol (Yafizham and M Abubakar): Ultisol soil is low of macro and micro nutrient, pH and base saturation as well as high toxicity of Al and Fe. To increase productivity of ultisols soils, especially availability of P nutrients, the use  of bio-phosphate can increase P solubilizing in the soils. The research was conducted in the green house of Agriculture Faculty, the University of Lampung from January to March 2005.  A factorial experiment using two factors  in a randomized completely block design with five replications was conducted.  The first factor was dosages of bio-phosphate (0; 10; 20 g L-1), the second factor was lowland rice cultivar (Ciherang, Sintanur, Cilosari and IR64).  The results showed that the availability of N, K and P nutrients in the soil before planting was low. Application of bio-phosphate increased availability of N, K and P in the soil. Application of 10 g L-1 and 20 g L-1 of bio-phosphate increased root length of lowland rice, there were 13.3% and 36.8%, respectively. Application of 20 g L-1 of bio-phosphate increased 100 grain weight of lowland rice which were higher 11.4% compared to without any bio-phosphate.